Effects of Exogenous Acetate and Glicose Load on Rate of Recycling between Acetate and Acetyl-CoA and Portal Drained Viscera of Sheep - Bugi Rustamadji (Faculty of Animal Science, Universitas Gadjah Mada, 1996)
Artikel dalam bentuk PDF